Determinants of maize marketing decisions for smallholder households in Tanzania - Lowe, Caitlin Heather (Kansas State University, 2013)
Smallholder farmers in Tanzania remain susceptible to food insecurity and poverty. To combat these challenges, the country and development organizations have turned to agriculture. In particular, value chains have been identified as a point of interest. Specifically, the maize value chain is of critical importance since maize is the staple crop of the country as well as the staple carbohydrate in the Tanzanian diet. Markets are beneficial because they enable households to specialize in agricultural production according to their comparative advantage. Specifically, markets have been shown to be one tool for increasing welfare, measured through the proxy income. The objective of this thesis is to identify the determinants of a household’s decision to participate in the maize market as well as identify the determinants of a household’s decision regarding how much maize to sell in a given market. This research examines formal and informal market participation among 908 households during the 2008 long rainy season. Probit models were estimated to determine market participation for the formal, informal, and aggregate sale market levels. A Heckman OLS model was used to further analyze the value sold by the household in a given market. Econometric results indicate that “quantity harvested” positively and significantly impacts market participation decisions as well as value sold decisions. The variable “male-headed households” was positive and significant in the formal market while the variable showed no significant impact in the informal market participation model. Both “radio ownership” and “mobile telephone ownership” proved to be positive and significant in the formal model while only the ownership of a radio was significant in the informal market. Additionally it was found that for the formal market participation decision, “bicycle ownership” was positive and significant. Overall, it appears that households participate in the informal market as a way to meet cash needs since farmers were not price-responsive. However, in the formal market farmers were found to be very price-responsive, following neo-classical economic theory.
Keywords: Market participation; Maize; Tanzania; Economics, Agricultural (0503)